Efecto del silicio en el crecimiento, productividad y calidad nutracéutica del tomate (Solanum lycopersicum L) - Tipán Torres, Hilda Cristhina (2022)
The importance of silicon is increasing today due to its abundance in nature and its proven beneficial effects on plants. The objective of this research was to evaluate the effect of three doses of silicon on the growth, productivity and nutraceutical quality of tomato, cultivar Acerado 3059. The research was carried out in the greenhouse of the Experimental campus "La María", in Mocache, province of Los Rios, Ecuador. In a completely randomized design, three doses of silicon were evaluated at 0.15; 0.25 and 0.35 g.plant-1, plus a control without application, for a total of four treatments, with four replicates, each made up of 10 plants, for a total of 40 plants per treatment.